On the prediction of systemic risk tolerance of cryptocurrencies - Boubaker, Sabri; Sitara, Karim *; Naeem, Muhammad Abubakr; Rahman, Molla Ramizur (Elsevier, 2024)
The role of big data in finance is pivotal, especially in forecasting stock prices, mitigating risk, and assessing market anomalies. With the financial system becoming more interconnected, analytical models using large data are gaining prominence in developing risk spillover models. This study estimates the systemic risk tolerance of twenty-five high-valued cryptocurrencies and finds that Fantom has the highest tolerance, while Bitcoin and Ethereum have a lower tolerance due to their large market share. It also shows that the common trend of cryptocurrencies enhances each other's tolerance and develops a predictive model for systemic risk tolerance. The study can help investors and market participants devise strategies for safe haven investment, hedging, and speculation during a market downturn.